(3fOhI eMGVQGJ aj GdJShjb (B: s (3eWHhYI ehLgI dWdHI GdSfI GdKGdKI Ydhe JLGQjI, JNUU(B: (3JShjb(B:(3eWHhYI (B/ s - (3MaUj, gOis; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2023)
(3GdJShjb GdGNVQ,GdJShjb GdGLJeGYj,GdJShjb GdCNdGbj,GdeSDhdjI GdGLJeGYjI ddJShjb,GdJShjb GdeSJOGe,GdJShjb GdGHJcGQj,GdJShjb GdGdcJQhfj,GdJShjb YHQ GdgGJa GdfbGd,GOGQI YdGbGJ GdRHGFf GdGdcJQhfjI,GdGJUGdGJ GdJShjbjI GdeJcGedI,GdJShjb GdTHcj(B.s
(3GdeQGLY U(B.117s
Keywords: (3GdJShjbs